Study of Professions from the Discipline Approach to Business Administration in the Tuning project in Latin America (GEON Journal (Management, Organizations and Business), 2017)
The study of the professions has gone through several historical moments, from conceptual to academic and with diverse approaches, from a critical social analysis, to the capitalist and at the moment to a state of knowledge that has scarcely been worked in Mexico, but that has served as a base for the path of the curriculum in Higher Education as a bridge between the profession and the graduate from the characteristics that emanate from it; Thus, from the point of view of the economic-administrative area, this research deals with. Alluding to the profession Agüero Aguirre, (2003) establishes characteristics of a context that determines the national and international environment of the demands of the administrator, to lead it to the path of the curriculum.
Keywords: Professions; Administration; Project tuning